Why do pharmacists leave the profession? A mixed-method exploratory study - Trudi J. Aspden; Pushkar R. Silwal; Munyaradzi Marowa; Rhys Ponton (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Recent New Zealand policy documents aim for pharmacists to be retained, and promote the provision of extended clinical pharmacy services. However, younger pharmacists have expressed dissatisfaction with the profession on informal social for a. Objectives: To explore the characteristics, and perspectives of pharmacy as a career, of recent Bachelor of Pharmacy (BPharm, four-year degree) graduates who have left, or are seriously considering leaving the New Zealand pharmacy profession in the near future and where they have gone, or plan to go. Methods: We conducted a cross-sectional study with a mixed-method explanatory sequential design. An anonymous online survey among those who completed their pharmacy undergraduate degree (BPharm or equivalent) in 2003 or later and who had left or who were seriously considering leaving the New Zealand pharmacy profession in the next five years, was open from 1st December 2018 to 1st February 2019. Recruitment occurred via University alumni databases, pharmacy professional organisations, pharmaceutical print media, social media and word-of-mouth. Ten semi-structured interviews were then conducted with a purposive sample of survey respondents. Descriptive statistics were generated from the quantitative data and qualitative data were analysed using manifest content analysis. Results: We received 327 analysable surveys of which 40.4% (n=132) were from those who had already left the New Zealand pharmacy sector at the time of the data collection and the rest (59.6% n=195) were those working within the sector, but seriously considering leaving the profession. Reasons most commonly reported for studying pharmacy were having an interest in health and wanting to work with people. The most common reasons for leaving, or wanting to leave, were dissatisfaction with the professional environment, including inadequate remuneration, and a perceived lack of career pathways or promotion opportunities. A wide range of career destinations were declared, with medicine being most frequently reported. Conclusions: Most of the reasons for leaving/considering leaving the profession reported relate to the values and features of the pharmacy profession such as the professional environment, remuneration and career pathways. These findings are consistent with other studies and may represent a barrier to achieving the aims of recent health policy documents.